Modern reception of ancient Ukrainian mythology of Аleksandr Denysenko’s prose - Соколова, Алла Василівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The article studies the mythological space of the book of the contemporary Ukrainian writer and scriptwriter А. Denisenko “The Soul of the River”. The focus is drawn to the conceptual framework of the mythopoetic world as an integral literary system. According to the author, А. Denisenko skillfully interweaves the plots and the images of the Slavic heathen beliefs into his text and, therefore, becomes the demiurge of his own mythology, the creator of the fairy tale, where the ordinary and the sacred are tightly intertwined. The writer combines the past and present of the Ukrainian village, appealing to the ethnoreligious codes, and creates his own conception of the myth as a mode of modern thinking.